Acoustic environment in wooden offices a comparison of perceived sound environment between wooden and concrete office buildings - Nobelius, Emilia; Ståhl, Isabella (My University, 2023)
Building in wood is becoming increasingly popular, and acousticians face new challenges regarding the indoor sound environment. The knowledge about the acoustic environment in wooden offices is not meeting the increasing demand, hence more studies on the subject are needed. Up till now, most office buildings are constructed in concrete, but a shift in mindset within the building industry has created already noticeable changes towards constructing larger buildings in wood. This thesis investigates the acoustic environment in wooden offices to identify differences in wooden and concrete buildings, find correlations between the perceived acoustic quality and the measured, as well as learn how the employees in the office perceive the acoustic environment. The thesis is made in collaboration with Efterklang part of AFRY. A total of eight offices located in different parts of Sweden have been investigated, out of which four are wooden buildings.The methods used to investigate the problem formulation are a questionnaire survey, an analysis of collected available measurement data for the buildings and a literature study. The questionnaire survey was distributed to employees in the eight buildings, and aimed to learn how they perceived the acoustic environment of their office. In the literature study differences between the acoustics in wooden and concrete constructions were identified. For wooden constructions it is impact noise and low frequency sounds that are a common problem, while the sound insulation at high frequencies usually is good. For concrete buildings these problems are not as common due to a larger amount of existing knowledge. In the results from the questionnaire and collected available measurement data it was shown that the employees overall perceive their offices to have a good acoustic environment. It was also found that the most disturbing source, regardless of building type, are colleagues talking on the phone (including Teams, Zoom etc.) and colleagues talking to each other. Impact noise was chosen by a third of the respondents in the wooden offices as one of the more disturbing sources, but a fourth of the respondents answered that they were not disturbed by anything. Overall the responses show a positive view on the acoustics in wooden offices.
Keywords: acoustic environment, wooden office buildings, concrete office buildings, sound perception, questionnaire survey